Pre-emptive Use of Riboflavin in a Rat Model of Bilateral Cavernous Nerve Injury - ŞENER, GÖKSEL; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE (GALENOS YAYINCILIK, 2018)
Objective: Erectile dysfunction is commonly encountered after radical prostatectomy due to cavernous nerve injury (CNI). We investigated the effects of riboflavin (Rb) on bilateral CNI in a rat model. Materials and Methods: Twenty-four male rats were divided into four groups: control (C), patients with bilateral CNI, those with CNI receiving postoperative Rb treatment (CNI+Rb), and those with CNI receiving pre- and post-operative Rb treatment (Rb+CNI+Rb). Bilateral CNI was performed in all groups except for C. The CNI+Rb group was treated with 30 mg/kg Rb daily after CNI for two weeks; the Rb+CNI+Rb group was treated with 30 mg/kg Rb daily one week before CNI and then for two weeks after injury. Mean arterial pressure (MAP) and intracavernosal pressure (ICP) were measured 14 days after CNI in all groups. Tissue malondialdehyde, cyclic guanosine monophosphate, nerve growth factor, superoxide dismutase and total nitric oxide synthase (NOS) activities, neuronal NOS (nNOS) and inducible NOS (iNOS) were analyzed. Results: ICP/MAP ratio was significantly lower in the CNI (p<0.01) and CNI+Rb groups (p<0.05) compared to the control group, however, the Rb+CNI+Rb group had results comparable to the C group in terms of nNOS and iNOS expression in the Western Blot analysis. Conclusion: Rb exerted anti-oxidative and anti-inflammatory effects on CNI in a CNI rat model. Rb can be a potential beneficial agent to improve erectile function in nerve-sparing radical prostatectomy patients as a preemptive penile rehabilitation strategy, although further clinical studies are needed.
Keywords: Cavernous nerve injury; Erectile dysfunction; Oxidative stress; Riboflavin; SPINAL-CORD-INJURY; RADICAL RETROPUBIC PROSTATECTOMY; ENDOTHELIAL GROWTH-FACTOR; ERECTILE DYSFUNCTION; NEUROTROPHIC FACTOR; PENILE INNERVATION; BONE-MARROW; CELLS; RECOVERY; FK506